Chemical composition, structural and functional properties of insoluble dietary fiber obtained from the Shatian pomelo peel sponge layer using different modification methods. (1st August 2022) - Sang, Jiaqi; Li, Lu; Wen, Jing; Liu, Haocheng; Wu, Jijun; Yu, Yuanshan; Xu, Yujuan; Gu, Qingqing; Fu, Manqin; Lin, Xian
Abstract: In order to improve the function of Shatian pomelo sponge layer insoluble dietary fiber (IDF), it was modified by high hydrostatic pressure (HHP, 400 MPa, 15 min), cellulose hydrolysis (CH, 0.4% cellulase, 70 min) and alkaline hydrolysis (AH, 1.4% sodium hydroxide solution, 20 min), respectively. Compared with the unmodified IDF, the molecular weight and particle size of the three modified IDFs were both decreased, while their void structure was increased. Specifically, the IDF treated with AH resulted in the smallest particle size (60.63 μm) and a honeycomb-like void structure, which explained why AH-treated IDF showed the strongest glucose and cholesterol adsorption capacities in vitro. The contents of rhamnose, xylose, galactose and galacturonic acid in IDF were significantly increased after HHP treatment (H-IDF). Moreover, H-IDF and CH-treated IDF (C-IDF) exhibited similar capacities for oil-holding and cation-exchange. H-IDF presented the strongest swelling capacity and excellent capacity for cholesterol adsorption. Thus, HHP modified Shatian pomelo peel sponge layer IDF can not only improve the utilization of by-products, but also has potential application value as a novel ingredient in hypolipidemic and hypoglycemic foods products. Highlights: Three modification methods had effect on color of insoluble dietary fiber (IDF). The alkaline hydrolysis (1.4% sodium hydroxide solution, 20 min) treatment significantly reduces the crystalline value of IDF. The water holding capacity of IDF could increase by 101.5% after High hydrostatic pressure (HHP, 400 MPa, 15 min) treatment. Surface morphology and main structure of IDFs were obviously changed by three kinds of modifications. IDF has higher cholesterol adsorption capacity after HHP treatment.